2009
DOI: 10.1096/fj.08-118042
|View full text |Cite
|
Sign up to set email alerts
|

Pichia pastorisas a host for secretion of toxic saporin chimeras

Abstract: Most of the targeting moieties, such as antibody fragments or growth factor domains, used to construct targeted toxins for anticancer therapy derive from secretory proteins. These normally fold in the oxidative environment of the endoplasmic reticulum, and hence their folding in bacterial cells can be quite inefficient. For instance, only low amounts of properly folded antimetastatic chimera constituted by the amino-terminal fragment of human urokinase (ATF) fused to the plant ribosome-inactivating protein sap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 41 publications
0
66
0
Order By: Relevance
“…Saporin is a plant toxin belonging to the type 1 family of RIPs that lack a B chain and bind cell surfaces with difficulty, although in the case of saporin it was described that it can bind the ␣2 macroglobulin receptor unequally distributed in different types of cells (12). Intracellular trafficking of saporin has not been fully elucidated yet, but it does not require intracellular reduction to intoxicate the target cell.…”
Section: Resultsmentioning
confidence: 99%
“…Saporin is a plant toxin belonging to the type 1 family of RIPs that lack a B chain and bind cell surfaces with difficulty, although in the case of saporin it was described that it can bind the ␣2 macroglobulin receptor unequally distributed in different types of cells (12). Intracellular trafficking of saporin has not been fully elucidated yet, but it does not require intracellular reduction to intoxicate the target cell.…”
Section: Resultsmentioning
confidence: 99%
“…The instability of the protein may be due to the effect of proteases, which are also secreted from Nevertheless, the rt-PA yield was significantly higher than the tPA production (up to 0.017%) in a hairy root system (54). Unlike tPA, reteplase has no carbohydrate side chains, and thus can be produced in E. coli cells, but most of the protein is present as an inclusion body, making its extraction and renaturation a time to consume downstream process, involving solubilization and protein refolding and dialysis (55). The culture medium could be optimized e.g.…”
Section: Determination Of the Protein Content And Activity Assay Of Pmentioning
confidence: 99%
“…While the inclusion of the spacer generally enhances the cleavage efficiency of this endopeptidase specific for dibasic sites, several studies have demonstrated problems with the subsequent proteolytic processing of the EA repeats. [54][55][56]76 Apparently, the quantity and/or activity of the STE13-encoded DPAPase A in the secretory pathway is not sufficient to process these repeats for large amounts of recombinant protein expressed under strong promoters. The resulting secretion of molecules with amino-terminal EAEA extensions was also observed for both the heavy and the light chains of the initial IgG constructs expressed in the Pichia system in this study.…”
Section: Glycan Structuresmentioning
confidence: 99%